Experimental investigation of associative polymer performance for CO2 foam enhanced oil recovery - Ahmed, S. (Elsevier B.V., 2017)
Polymer addition amplifies the foam flood performance by providing a substantial mobility control during the enhanced oil recovery (EOR). A conventional anionic polymer i.e. hydrolyzed polyacrylamide (HPAM) is widely used for polymer enhanced foam (PEF) flooding. In this study, the foam stability and viscosity performance of the conventional HPAM polymer were compared with a relatively new associative polymer. An associative polymer (i.e. Superpusher B 192) and the conventional polymer of same molecular weight were considered and the foam generation was performed using a widely used foamer i.e. alpha olefin sulfonate (AOS) and a foam stabilizer (betaine). FoamScan was used to measure the foam stability whereas, for foam viscometric measurements, a high-pressure high-temperature foam rheometer was utilized. An associative polymer showed an interesting combination and both the apparent viscosity and foam stability were found to be significantly high. The conventional polymer failed to provide a high foam strength in rheometric analysis whereas, an associative polymer showed an interesting viscosity profile and a two-fold increase in the foam apparent viscosity was observed. This study shows that the associative Superpusher B192 holds a bright potential in increasing the foam flood performance during EOR. © 2017 Elsevier B.V.